2015
DOI: 10.1186/s12933-015-0196-1
|View full text |Cite|
|
Sign up to set email alerts
|

Type 2 diabetes-associated carotid plaque burden is increased in patients with retinopathy compared to those without retinopathy

Abstract: BackgroundCardiovascular disease (CVD) is the leading cause of mortality among subjects with type 2 diabetes (T2D), and diabetic retinopathy (DR) has been associated with an increased risk for CVD. The present study was designed to test the concept that T2D patients with DR, but without previous cardiovascular (CV) events and with normal renal function, have an increased atherosclerotic burden compared with patients without DR.MethodsA cross-sectional study was performed using patients with normal renal functi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
85
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 52 publications
(91 citation statements)
references
References 51 publications
6
85
0
Order By: Relevance
“…Many epidemiological studies showed that DR is associated with macrovascular diseases in patients with type 2 diabetes [47]. Patients with type 2 diabetes and DR have an increased presence and number of plaques in the carotid territory [48]. The presence of dyslipidemia (elevated triglycerides and decreased HDL cholesterol) is associated with silent myocardial ischemia or angiographic coronary artery disease in asymptomatic patients with type 2 diabetes [49].…”
Section: Discussionmentioning
confidence: 99%
“…Many epidemiological studies showed that DR is associated with macrovascular diseases in patients with type 2 diabetes [47]. Patients with type 2 diabetes and DR have an increased presence and number of plaques in the carotid territory [48]. The presence of dyslipidemia (elevated triglycerides and decreased HDL cholesterol) is associated with silent myocardial ischemia or angiographic coronary artery disease in asymptomatic patients with type 2 diabetes [49].…”
Section: Discussionmentioning
confidence: 99%
“…The study design and assessment of the cohort participants have been described previously by our group in a previous study (20) in which the presence and extension of carotid plaques were analyzed in patients with type 2 diabetes with and without DR. The inclusion criteria for both groups were as follows: age range 40-75 years; absence of established impaired renal function (calculated glomerular filtration rate ,60 mL/min); and absence of known CV disease.…”
Section: Subjectsmentioning
confidence: 99%
“…The clinical examination and review of patients' clinical records ruled out heart failure, any previously known CV events or associated revascularization procedures (coronary heart disease, cerebrovascular disease, and peripheral vascular disease, including previous diabetic foot disease). The general clinical, laboratory, and carotid ultrasound procedures have been described in detail elsewhere (20). Briefly, 312 patients with type 2 diabetes without previous CV events and with normal renal function were recruited from the outpatient clinic at our center.…”
Section: Subjectsmentioning
confidence: 99%
“…The consequences of delayed detection of DR extend beyond suboptimal visual acuity outcomes; increasing evidence links retinopathy to other microvascular complications of diabetes, most notably nephropathy and cardiac autonomic neuropathy (CAN) . Retinopathy has also been linked to macrovascular comorbidities, including stroke, myocardial infarction and, potentially, heart failure . Additionally, a recent meta‐analysis of epidemiological observational studies found that patients with diabetes who have DR are at increased risk of all‐cause mortality, compared with patients with diabetes who do not have retinopathy (risk ratio [RR], 2.33; 95% CI, 1.92‐2.81) …”
Section: Introductionmentioning
confidence: 99%
“…With regard to the link between DR and cardiovascular events, Alonso et al conducted a cross‐sectional study of patients with T2DM who did not have renal deficits or prior history of cardiovascular disease (CVD). They found that the percentage of patients with carotid plaques, a risk factor for ischaemic stroke, was higher among those with DR than among those without DR (68.0% vs 52.2%; P = 0.0045) . Other research has demonstrated that, not only is DR associated with future cardiovascular events, but also that the risk of these events increases with increasing severity of DR (hazard ratio [HR], 1.49; 95% CI, 1.12‐1.97 for mild retinopathy and HR, 2.35; 95% CI, 1.47‐3.76 for severe retinopathy) .…”
Section: Introductionmentioning
confidence: 99%